2018
DOI: 10.1007/s10799-018-0287-2
|View full text |Cite
|
Sign up to set email alerts
|

The impact of technology capability, human resources, internationalization, market resources, and customer satisfaction on annual sales growth rates of Korean software firms

Abstract: This study investigates the competitive factors of software firms that participated in the Korea Software Firm Competitiveness Awards, a nationwide project supported by the Ministry of Knowledge Economy that studies the performance of software firms in Korea. The study applies concepts from hierarchical multiple regression analysis to develop a model to assess the relationship between the competitive factors of software firms and firm performance. The developed model was validated through a field survey of 79 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…The competitive environment in which new ventures operate changes quickly and frequently and new ventures must promptly respond to the competitive changes [13,14]. It is important to understand how new ventures can most effectively use their capabilities to achieve sustainability of growth and performance in high versus low competitive environments [3,[15][16][17]. Accordingly, prior studies have suggested that analysis of the capabilities-performance relationship should consider the potential moderating effects of complex competitive conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…The competitive environment in which new ventures operate changes quickly and frequently and new ventures must promptly respond to the competitive changes [13,14]. It is important to understand how new ventures can most effectively use their capabilities to achieve sustainability of growth and performance in high versus low competitive environments [3,[15][16][17]. Accordingly, prior studies have suggested that analysis of the capabilities-performance relationship should consider the potential moderating effects of complex competitive conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…In Various studies have supported findings of this study that IT capability has a positive relationship with firm market share and that organisational culture moderated the relationship between IT capability and performance indicator like market share especially in today's dynamic business environment (See Chege, Wang & Suntu, 2019;Macharia, Mike, Ondabu & Kepha, 2015;Turulja & Bajgorić, 2016). Further majority of scholars in different economies strongly have established that organisational culture and information technology capability were major determinants of firm overall performance due to the continuous pace of globalisation and dynamics that characterised 21st century business environment (Djaja & Arief, 2015;Kipyegon, Obura & Oginda, 2018;Lee, Leem & Bae, 2018;Lu & Ramamurthy, 2011;Mavengere, 2013;Mao, Liu & Zhang, 2015;Ockley, Senaji & Kiyanjui, 2017). Salehzadeh, Pool, Mohseni and Tahani (2017) have showed that organisations must pay adequate attention to the development of an effective organisational culture, and facilitating the process of knowledge sharing and organisational agility which can lead to increased organisational performance.…”
Section: Model Specificationmentioning
confidence: 99%
“…Arising from organisational culture rigidity among oil and gas firms in Nigeria, most of these firms cannot easily respond to future and business challenges and uncertain environment surrounding oil and gas industry, thus reduced oil and gas marketing market share in Nigeria. Majority of studies such as (Arokodare, 2019;Chen, Wang, Nevo, Jin, Wang & Chow, 2014;Kipyegon, Obura & Oginda, 2018;Lee, Leem & Bae, 2018;Lu & Ramamurthy, 2011;Mavengere, 2013;Mao, Liu & Zhang, 2015;Ockley, Senaji & Kiyanjui, 2017;Panda & Rath, 2016;Rahim & Zainuddin, 2019;Rehman, Mohd Nor, Taha & Mahmood, 2018;Turulja & Bajgoric, 2016) have examined how IT capability affects firm performance in different sectors; but most of these studies have never investigated how IT capability affect firm performance proxy with market share of oil and gas marketing companies in Nigeria. Additionally, these past studies have not considered how organisational culture moderates between IT capability and firm performance in terms of market share of oil and gas marketing companies in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is presented, in particular, in several studies (e.g. KucharÄŤĂ­ková et al, 2018;Lee et al, 2018). It is also important to rely on the research process of the works which deal with the analysis and formation of the models associated with an effective innovation process in the developed countries, (Lema et al, 2018;Seidel-Sterzik et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%